Toward Data‐Driven Applications in Lithium‐Ion Battery Cell Manufacturing. Issue 2 (13th May 2019) - Turetskyy, Artem; Thiede, Sebastian; Thomitzek, Matthias; von Drachenfels, Nicolas; Pape, Till; Herrmann, Christoph
Abstract : Production chain of lithium‐ion battery cells is a highly complicated system with manifold process–product interdependencies and high sensitivity to ambient conditions. This complexity makes it harder to control and regulate economic and environmental target criteria (e.g., product quality, cost, and energy demand). Therefore, it is necessary to develop a holistic system understanding and to identify and evaluate the interactions between the process steps within the production chain of battery cells and their effects on the relevant cell properties. In this study, a data‐driven concept to acquire relevant data along the production line, including technical building services and cell diagnostics, is presented. Furthermore, it describes the combination of automated and manual data acquisition as well as merging of data from different sources, of different communicational protocols, and of different formats toward accessibility, convenient data management, and visualization. Abstract : Production chain of lithium‐ion battery cells is a highly complicated system, which makes it difficult to control and regulate economic and environmental target criteria (e.g., product quality, cost, and energy demand). This study presents a data‐driven concept for data acquisition, data management, and analysis, to enable the control and regulation of these criteria.